Training on Infant and Young Child Feeding (IYCF) for Mothers in Sepan Lebang Village, Sintang Regency - Anggerainy, Shinta Widiastuty; Mohamad Ikhsan; Huda, Siti Nurul (Teumulong: Journal of Community Service, 2024)
Good and essensial nutrition has influence for children's growth and development. Infant and young children's nutritional needs will fulfilled by providing appropriate nutrition and appropriate feeding stages. IYCF requires skills. For this reason, it is necessary to provide knowledge and training related to IYCF, especially for mothers, prospective mothers, and cadres. The community in Sepan Lebang Village has never received training regarding IYCF. This activity aims to increase mothers' knowledge and skills about IYCF. This activity began with providing education about IYCF which was attended by 37 mothers, and IYCF training which was attended by 15 mothers. The training was carried out twice with material related to breast milk (how to express and practice giving breastfeeding), material related to complementary feeding (the practice of preparing menus according to the stages of child feeding), feedback, and evaluation of the practice of giving breastfeeding and complementary feeding. The results of this activity show that from the knowledge aspect, mothers have knowledge about IYCF in improving children's quality of life. From the skills aspect, the majority of mothers are already skilled in carrying out the ability to practice providing good and correct positions and attachments, but a small number of mothers still need to do a lot of practice to improve these practical skills. For menu preparation skills, all participants can prepare menus properly and correctly according to the stages of infant and young child feeding.